A Critical Analysis of the French Language's Improperness as an Official Tongue in Contemporary Francophone West Africa: Exploring the Cultural, Social, Economic, and Political Implications for Locals - Simuziya, Nsama Jonathan (Вісник гуманітарних наук, 2025)
In Africa, colonialism has left many cursed legacies in its wake with far-reaching implications for the cultural, social, economic, and political life of locals. The use of colonial language as an official tongue of government business is a factor with enduring negative consequences for locals, but which do not appear obvious on face value. In Francophone West Africa, the French language was impishly presented as performing an innocuous and benign function in local societies. Yet, behind the veil, there were ominous and nefarious motives at play. The French colonial authorities imposed French as an official language, purportedly to operate as a neutral language on account that there were several indigenous languages. The central pivot of any culture is language, so by elevating the French language over indigenous tongues, the colonialists were subtly but methodically supplanting local cultural and traditional values with French cultural values. This study argues that the French language was and has never been in congruence with the emancipatory aims of local African traditions, customs, and values, and as such, local people need to rise to the occasion and (re)claim their rightful position as legitimate agenda setters of their polities. Data for this study were gathered through document analysis, digital ethnography, and online information relating to current developments in Francophone West Africa. Findings suggest that far from being a neutral language, French has been a major destabilizing factor in undermining the cultural, social, economic, and political life of the people of West Africa, especially by entrenching their marginalization. Further, the continued imposition of French is inconsistent with relevant United Nations (UN) human rights conventions on the fundamental rights of indigenous peoples in terms of the usage and promotion of their languages as mediums of official communication. Furthermore, the study exposes the spurious democracy mantra of France in Africa, whereby French pronouncements emphasizing the value of democracy have largely been a smokescreen for France’s furtherance of its neocolonial agendas of dominance, repression, economic colonization, forcible assimilation, and the divide-and-rule tactics of pitting local ethnicities against each other to create enmity. None of the aforementioned practices resembles democratic values; for there can be no genuine political democracy without relational equality in society. The study concludes that to reverse this foreign dominance trap that has continued to entrench inequalities, West African states should, in the interim, elevate their indigenous languages to the status of official tongues alongside French, with the ultimate objective of eventually dropping French altogether at some future point. Already, Mali has led the way; in 2023, it discarded French as an official language and replaced it with indigenous languages.